2018
DOI: 10.1101/451823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arginine methylation of DDX5 RGG/RG motif by PRMT5 regulates RNA:DNA resolution

Abstract: Aberrant transcription-associated RNA:DNA hybrid (R-loop) formation often lead to catastrophic conflicts during replication resulting in DNA double strand breaks and genome instability. To prevent such conflicts, these hybrids require dissolution by helicases and/or RNaseH. Little information is known about how these helicases are regulated. Herein, we identify DDX5, an RGG/RG motif containing DEAD-box family of RNA helicase, as a crucial player in R-loop resolution. We define at the mechanistic level the func… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(98 citation statements)
references
References 66 publications
(98 reference statements)
11
87
0
Order By: Relevance
“…In human cells, mtSSB has been reported to localize partially to RNA granules (64), whilst defects in the machinery of RNA processing and degradation results in the accumulation of persistent R-loops, resulting in RNase H1 recruitment to nucleoids (65). In an earlier study, vertebrate RNase H1 was not observed as a nucleoid protein (66), consistent with its interactions with mitochondrial replication and RNA processing enzymes being transient, and mediated by its association with RNA/DNA hybrid substrate, rather than by direct protein-protein interactions Amongst other nuclear hits, we identified a second component of the R-loop processing machinery, Rm62, the Drosophila homologue of human DDX5 (67). This suggests a potential interaction between two independent machineries to resolve R-loops.…”
Section: Significance Of Rnase H1 Interactorssupporting
confidence: 73%
“…In human cells, mtSSB has been reported to localize partially to RNA granules (64), whilst defects in the machinery of RNA processing and degradation results in the accumulation of persistent R-loops, resulting in RNase H1 recruitment to nucleoids (65). In an earlier study, vertebrate RNase H1 was not observed as a nucleoid protein (66), consistent with its interactions with mitochondrial replication and RNA processing enzymes being transient, and mediated by its association with RNA/DNA hybrid substrate, rather than by direct protein-protein interactions Amongst other nuclear hits, we identified a second component of the R-loop processing machinery, Rm62, the Drosophila homologue of human DDX5 (67). This suggests a potential interaction between two independent machineries to resolve R-loops.…”
Section: Significance Of Rnase H1 Interactorssupporting
confidence: 73%
“…The helicase Rm62 interacts genetically with both PcG and TrxG genes, and colocalizes with the PRE-binding protein Dsp1 on polytene chromosomes 38 . Rm62 is the Drosophila homologue of the DDX5 helicase, which can unwind RNA-DNA hybrids in vitro and is implicated in R-loop resolution in vivo 39 . A recent genome-wide RNAi screen for TrxG interacting genes (which should antagonize PcG function) identified the gene for RNaseH1 40 .…”
Section: Discussionmentioning
confidence: 99%
“…While this work used normally cultured, unperturbed human cells, many studies have used S9.6-based imaging to measure changes in RNA:DNA hybrid content under various experimental conditions. An array of gene perturbations and drug treatments have been reported to cause changes in S9.6 IF signal attributed to altered R-loop metabolism or RNA:DNA hybrid levels [8,30,[34][35][36][47][48][49][50]. Many of the genes that have been ascribed roles in R-loop regulation participate in diverse RNA metabolic processes like transcription, RNA splicing, RNA processing, and RNA export [6].…”
Section: Discussionmentioning
confidence: 99%